Recrutement de la morue arctique Boreogadus saida : climat, productivité et prédation - LeBlanc, Mathieu (Université Laval, 2019)
In the Canadian Arctic, climate change pressure is increasing, while anthropogenic activities and the resulting human impacts on the ecosystem are intensifying. However, fish communities remain poorly documented despite their pivotal role in the ecosystem equilibrium in transferring the energy from zooplankton to top arctic predators. The main objective of this PhD thesis is to document spatial and temporal variations in polar cod Boreogadus saida recruitment in the Canadian Arctic, and the environmental and biological factors influencing these variations. Based on fish abundance and biomass estimated with hydroacoustic data validated by nets and trawls from 2005 to 2017, I investigate: (1) the impacts of an earlier ice breakup and warmer sea surface temperatures (SST) on the survival and recruitment of age-0 polar cod in different regions of the Canadian Arctic; (2) the role of ecosystem productivity in age-0 polar cod recruitment and differences in productivity across three oceanographic provinces of the Canadian Arctic; and (3) the co-distribution of polar cod and its seabird predators across the marginal ice zone in Baffin Bay. Earlier ice breakup in the Canadian Arctic resulted in warmer SST in spring-summer, earlier phytoplankton bloom and higher ecosystem productivity in summer. Early ice breakup also increased juvenile polar cod biomass at the end of summer by allowing the survival of larvae hatched in winter and spring. In light of these results, it seems that both warm temperatures and, mostly, abundant food resource allow age-0 individuals to benefit from an earlier ice breakup, at least for the time being. During the period of the study, ecosystem productivity was similar in the southern Beaufort Sea and the North Water/Lancaster Sound polynya complex, but juvenile polar cod biomass was higher in the Beaufort Sea. Intense avian predation could explain the lower biomass of juvenile cod in the polynya complex, confirming its reputation as a biological hotspot for the transfer of energy to higher ...